PENGARUH KEGIATAN BERSAJAK TERHADAP KEMAMPUAN LITERASI DINI ANAK USIA 5-6 TAHUN DI TK TUNAS HARAPAN GBKP PEKANBARU - Lauren Afrylisa Kaban; Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem in this study is the lack of emergent literacy skills namely the ability to read and write the beginning of the children aged 5-6 years in Tunas Harapan Kindergarten GBKP Pekanbaru. This study aims to determine the effect of rhyme activity on emergent literacy ability of children aged 5-6 years in Tunas Harapan Kindergarten GBKP Pekanbaru. This research is an experimental research using one-group pretest-posttest desaign. The population in this study were children aged 5-6 years, amounting to 31 children and the sample used in this study is a sample saturated with a sample of 17 children. Data collection techniques used are observation. Data analysis technique using t-test. Based on the results of data analysis obtained tcount ꞊22,922 bigger than ttable ꞊ 2,120 (22,922> 2,120) with big significant 0,05. Thus it means there is a significant difference between before and after conducting experiments by applying rhyme activities. So it can be concluded that there is influence of rhyming activity on emergent literacy ability of children aged 5-6 years in kindergarten Tunas Harapan GBKP Pekanbaru with big influence 45,74%.Key Word: Emergent Literacy, Rhyming.